2003
DOI: 10.1126/science.1079666
|View full text |Cite
|
Sign up to set email alerts
|

PDGFRA Activating Mutations in Gastrointestinal Stromal Tumors

Abstract: Most gastrointestinal stromal tumors (GISTs) have activating mutations in the KIT receptor tyrosine kinase, and most patients with GISTs respond well to Gleevec, which inhibits KIT kinase activity. Here we show that approximately 35% (14 of 40) of GISTs lacking KIT mutations have intragenic activation mutations in the related receptor tyrosine kinase, platelet-derived growth factor receptor alpha (PDGFRA). Tumors expressing KIT or PDGFRA oncoproteins were indistinguishable with respect to activation of downstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
1,502
8
47

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 2,142 publications
(1,589 citation statements)
references
References 14 publications
32
1,502
8
47
Order By: Relevance
“…Mutation analyses of KIT and PDGFRA genes GIST tumors were analysed for mutations in exons 9, 11, 13 and 17 of the KIT gene and exons 12 and 18 of PDGFRA using a combination of denaturing high-performance liquid chromatography and direct sequencing, as previously described (Heinrich et al, 2003).…”
Section: Rt-pcr Detection Of Fusion Transcriptmentioning
confidence: 99%
“…Mutation analyses of KIT and PDGFRA genes GIST tumors were analysed for mutations in exons 9, 11, 13 and 17 of the KIT gene and exons 12 and 18 of PDGFRA using a combination of denaturing high-performance liquid chromatography and direct sequencing, as previously described (Heinrich et al, 2003).…”
Section: Rt-pcr Detection Of Fusion Transcriptmentioning
confidence: 99%
“…However, radiation and chemotherapy provide a o10% response rate (Dematteo et al, 2000(Dematteo et al, , 2002. Imatinib mesylate (IM), an orally administered selective c-Kit/PDGFR tyrosine kinase inhibitor, abrogates cellular proliferation of GIST cells in culture (Tuveson et al, 2001) and inhibits the constitutively active phosphorylating activity of c-Kit and PDGFR by binding the adenosine 5 0 -trisphosphate (ATP) site preventing the activation of PI-3K and mitogenactivated protein kinase dependent pathways (Heinrich et al, 2003). A randomized trial of GIST patients treated with IM showed that 5% patients achieved a complete response, 47% partial response and 32% stable disease (Verweij et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Moreover, recent studies have described activating mutations of plateletderived growth factor receptor-alpha (PDGFRA) at exons 12 and 18 in a minor subset (approximately 5-7%) of GIST. 6 Although GISTs exhibit a spectrum of biologic behavior from benign to malignant, the molecular mechanism of tumor progression has not been fully clarified. Previous studies have reported the prognostic significance of tumor size, mitotic counts, tumor grade, Ki-67 labeling index (LI), 7 KIT mutation type, 4,8,9 p16 inactivation 10 and overexpression of cell-cycle regulators such as cyclin A, cyclin B1 and cdc2.…”
mentioning
confidence: 99%